The adsorption of Cadmium and Lead Ions from aqueous solutions using non living biomass of Phragmites australis - Abdallah , Khalid J.; Abdulhay , Hind Suhail (Iraqi Journal of Science, 2022)
Adsorption is a simplified new way, easy application , economical and environmentally friendly. In which the use of certain types of plants to remove or reduce toxic heavy metals from water. The current study involved the use of a non-living biomass as a powder for local plant available in the Iraqi environment is Phragmites australis .This the study showed the high ability of this plant to remove cadmium and lead ions from the aqueous solutions within variable experimental factors by column bed method which were used to test different sizes of plant powder were (500.1000, 1500 and 2000) μm . These sizes treated with initial concentration of Cd(II), Pb(II) was 25ppm , separately To test the optimum size for maximum adsorption and was 1000 μm . After that were tested different concentrations of Cd, Pb are (25, 50, 75, 100, 125,150,175,200)ppm with powder size of 1000 μm . And the optimum concentration was 100ppm. Different flow rates (0.5, 1, 1.5, 2) ml / min were tested with the powder size at 1000 μm and concentration for each metal was 100ppm and the optimum flow rate was 1 ml / min . All the experiments conducted at constant the mean of pH was 5, 32, temperature 22 ± 2 , contact time ranged (22-40) minutes. Results of statistical analysis showed that the optimum conditions of the maximum adsorption were at 1000 μm of powder size, 100ppm of initial metal concentration, flow rate of 1 ml / min and the high removal rates of cadmium and lead ions by P. australis were 95,16 % and 92.76% , respectively .